2018
DOI: 10.1038/s41390-018-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Children’s low-level pesticide exposure and associations with autism and ADHD: a review

Abstract: Pesticides are chemicals that are designed specifically for the purpose of killing or suppressing another living organism. Human toxicity is possible with any pesticide, and a growing body of literature has investigated possible associations with neurodevelopmental disorders. Attention deficit disorder with or without hyperactivity (ADHD) and autism spectrum disorder (ASD) are two of these specific disorders that have garnered particular interest. Exposure to toxic chemicals during critical windows of brain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 73 publications
0
45
0
Order By: Relevance
“…Compounds which have been classified as neurotoxic agents damage the brain or peripheral nervous system. They can induce neurological diseases, including attention-deficit hyperactivity disorder (ADHD), autism, Alzheimer's disease, and Parkinson's disease [98][99][100]. A reliable method to test compounds for neurotoxic characteristics is to perform HCS checking cell morphology, or neurite outgrowth [4,101,102].…”
Section: Neurotoxicity and Developmental Neurotoxicitymentioning
confidence: 99%
“…Compounds which have been classified as neurotoxic agents damage the brain or peripheral nervous system. They can induce neurological diseases, including attention-deficit hyperactivity disorder (ADHD), autism, Alzheimer's disease, and Parkinson's disease [98][99][100]. A reliable method to test compounds for neurotoxic characteristics is to perform HCS checking cell morphology, or neurite outgrowth [4,101,102].…”
Section: Neurotoxicity and Developmental Neurotoxicitymentioning
confidence: 99%
“…Most epidemiological studies conducted between 2006 and 2018 about ASD were mainly focused on a few pesticide groups, probably because they have been the most widely used since the mid-XIX century. These groups comprised of the organochlorines (OCs), organophosphates (OPs), pyrethroids and carbamates (Roberts et al, 2019). Almost all were case-control studies conducted in California (USA).…”
Section: I-introductionmentioning
confidence: 99%
“…Finally, numerous prospective birth-cohort studies conducted in the general population showed significant relationships between early exposure to pesticides and the onset of autistic behaviors or ASD-associated symptoms in healthy children (Eskenazi et al, 2007;Furlong et al, 2014;Brown et al, 2018;Sagiv et al, 2018). According to Roberts et al (2019), the results from the whole literature provided enough evidences that OCs, OPs, carbamates and pyrethroids may play a role in the ASD onset.…”
Section: I-introductionmentioning
confidence: 99%
“…These differences suggest diverse mechanisms for ADHD between the sexes. Several studies have reported possible mechanisms of ADHD, including environmental toxicity (Roberts et al, 2019 ), genetic factors (Hawi et al, 2015 ; Mogavero et al, 2018 ), epigenetic regulation (Tran and Miyake, 2017 ), neurotrophic factors (Tsai, 2017 ), and socioeconomic status (Russell et al, 2016 ). In related studies, a higher theta/beta ratio (TBR) in electroencephalography (EEG) bands was observed in the central area in patients with ADHD (Chabot and Serfontein, 1996 ; Arns et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%